Aggregation kinetics of polystyrene nanoplastics in gastric environments: Effects of plastic properties, solution conditions, and gastric constituents. (December 2022) - Shao, Zhiwei; Su, Jiana; Dong, Jiawei; Liang, Miaoting; Xiao, Jie; Liu, Jindie; Zeng, Qiaoyun; Li, Yongtao; Huang, Weilin; Chen, Chengyu
Graphical abstract: Highlights: Aggregation rate of PSNPs followed the order of NP100 > A-NP100 ≈ C-NP100 > NP500. Aggregation rate ranked order of SGF5 > SGF4 > SGF3 > SGF2 > SGF1 and pH 2 > 3.5 > 5. Increasing concentration of PSNPs enhanced aggregation rate in SGFs up to 13.82 nm/s. Sorption: lysozyme > porcine bile > proteose-peptone > pepsin > glycine > D-glucose. Electrostatic force and steric hindrance by protein corona affected PSNP aggregation. Abstract: Nanoplastics are inevitably ingested into human gastric environment, wherein their aggregation kinetics and interactions with gastric constituents remain unclear. This study investigated the early-stage (20 min) and long-term (1–6 h) aggregation kinetics of four commonly-found polystyrene nanoplastics (PSNPs) including NP100 (100-nm), A-NP100 (100-nm, amino-modified), C-NP100 (100-nm, carboxyl-modified), and NP500 (500-nm) under gastric conditions. Five simulated human gastric fluids (SGFs) including SGF1-3 (0–3.2 g/L pepsin and 34.2 mM NaCl), SGF4 (400 mM glycine), and SGF5 (nine constituents), three pH (2, fasted state; 3.5, late-fed state; and 5, early-fed state), and 1–100 mg/L PSNPs were examined. Aggregation rates ranked NP100 > A-NP100 ≈ C-NP100 > NP500, SGF5 > SGF4 > SGF3 > SGF2 > SGF1, and pH 2 > 3.5 > 5. Increasing PSNP concentration enhanced aggregation rate up to 13.82 nm/s. Aggregation behavior generally followed the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory. Pepsin, glycine, and proteose-peptone strongly influenced PSNP stability via electrostatic interaction and steric hindrance imparted by protein corona. Freundlich isotherm suggested that PSNPs adsorbed organic constituents following lysozyme > porcine bile > proteose-peptone > pepsin > glycine > D-glucose, inducing changes in constituent structure and PSNP properties. These findings provide insights on the transport of nanoplastics in the gastric environments.